Pemetaan Perkembangan Penelitian Sistem Plumbing Bangunan: Analisis Bibliometrik Dan Systematic Literature Review (2005–2025) - Herlan Herlambang (Nozel : Jurnal Pendididikan Teknik Mesin, 2026)
Building plumbing systems have gained increasing scholarly attention alongside the rise of sustainable construction, smart infrastructure, and digital building technologies. This study maps the development of research on building plumbing systems from 2005 to 2025 using an integrated approach combining bibliometric analysis and a systematic literature review. Data were retrieved from the Scopus database using keywords related to plumbing systems, water supply, drainage, smart plumbing, IoT, and digital twin technologies, with article selection conducted through the PRISMA framework. From 1,245 identified records, 612 peer-reviewed journal articles were included in the final analysis. Bibliometric techniques using VOSviewer and Biblioshiny were applied to evaluate publication trends, geographic and institutional contributions, citation performance, and keyword co-occurrence networks. Results indicate a consistent upward trend in publications, rising from 45 articles (2005–2010) to 259 articles (2021–2025). China emerges as the most productive country, while the United States demonstrates the highest citation impact. Keyword analysis reveals three main thematic clusters: water systems, sanitation and drainage, and modern plumbing technologies. The study also identifies key research gaps, including limited integration of artificial intelligence and machine learning, early-stage development of digital twin applications in plumbing systems, and insufficient empirical studies in tropical environments. These findings highlight critical directions for advancing intelligent, efficient, and sustainable plumbing system research